Analysis of Service Quality, Price and Customer Trust Towards Customer Satisfaction at Haji Mahmud Mushroom Chicken Noodles Medan - Irma Hajira; Nurafrina Siregar; Erwansyah, Erwansyah (INFOKUM, 2025)
This study aims to analyze the influence of service quality, price, and customer trust on customer satisfaction at Haji Mahmud Mushroom Chicken Noodles in Medan. The research uses a quantitative approach with a survey method. Data were collected through questionnaires distributed to 100 respondents who are customers of the restaurant. The data were then analyzed using multiple linear regression analysis to examine the relationship between the independent variables (service quality, price, and trust) and the dependent variable (customer satisfaction). The results of the analysis show that service quality, price, and customer trust have a positive and significant effect on customer satisfaction either partially or simultaneously. Among the three variables, customer trust has the most dominant influence on satisfaction. These findings indicate that maintaining service quality, offering competitive prices, and building customer trust are crucial strategies to enhance satisfaction and customer loyalty at Haji Mahmud Mushroom Chicken Noodles Medan.